A modified truncation singular value decomposition method for solving ill-posed problems. (November 2018) - Zhao, Zhenyu; Lin, Riguang; Meng, Zehong; He, Guoqiang; You, Lei; Zhou, Yongxiong
A modified truncated singular value decomposition method for solving ill-posed problems is presented in this paper, in which the solution has a slightly different form. Both theoretical and numerical results show that the limitations of the classical TSVD method have been overcome by the new method and very few additive computations are needed.